Habitats de inovação em ambientes urbanos sustentáveis - Motke, Francies Diego (2017)
Today, we live in an essentially urban environment. In recent years, there has been an accelerated process of urbanization around the world, occurring in both developed and developing countries, currently accounting for 54% of the world's population living in cities. This significant increase in population has led to several discussions about the challenges of urban management in this cluster. The planning of the coming years reminds us to reflect on the concept of sustainable development for urban centers and issues such as increased pollution, urban mobility, quality of life, energy management and availability of green areas will be on the agenda. The high concentration of people also provides some benefits, since large cities are the natural economic center of a large number of companies which, when inserted in a context conducive to innovation, where there is abundant knowledge and skills, acquire greater Efficiency in innovation. Therefore, the challenge is to promote an adequate management of the resources available in these cities, in order to promote a favorable environment that supports the growth of these environments and the emergence of innovations, considering the aspects of sustainable development. The present work had as objective to analyze the importance of the sustainable practices of management of the urban environments for the generation of innovation in companies located in habitats of innovation. For that, a research of qualitative approach, of exploratory nature, was developed through a study of multiple cases. Data analysis was done through content analysis and data interpretation was performed based on theoretical assumptions, comparing empirical data with expected patterns. The subjects investigated were the managers of 5 (five) companies residing in 3 (three) technological parks: Santa Maria Tecnoparque, Parque Tecnológico da PUCRS - Tecnopuc and Parque Tecnológico da UFRJ. The results show that the axes that have stood out the most and which may have an impact on the businesses investigated and generate innovations, concern (1) Governance, (2) Equity, Social Justice and Culture of Peace, (3) Urban Planning and Design, (4) Education for Sustainability and Quality of Life, (5) Local Economy, Dynamic, Creative and Sustainable Economy, and (6) More Mobility, Less Traffic. Thus, the assumption in the study, sustainable management practices of urban environments favor the generation of innovation in companies located in innovative habitats, from the context analyzed, is partially confirmed according to the evidence found. The limitations of this study point out that the results found represent only the subjects investigated, it is not possible to make use of generalizations, the results found are based only on the perception of the managers and other stakeholders involved were not investigated and the method used that does not allow some questions understood. As a suggestion for future studies, it is suggested the extension of the subjects investigated to other urban centers and other business models and the application of other research strategies to verify the importance of sustainable urban environment management practices in the development of innovation habitats.